Collaborative Brushing and Linking for Co-located Visual Analytics of Document Collections - Fisher, Danyel; Isenberg, Petra (Proceedings of Eurovis 2009, 2009)
Many real-world analysis tasks can benefit from the combined efforts of a group of people. Past research has shown that to design visualizations for collaborative visual analytics tasks, we need to support both individual as well as joint analysis activities. We present Cambiera, a tabletop visual analytics tool that supports individual and collaborative information foraging activities in large text document collections. We define collaborative brushing and linking as an awareness mechanism that enables analysts to follow their own hypotheses during collaborative sessions while still remaining aware of the group’s activities. With Cambiera, users are able to collaboratively search through documents, maintaining awareness of each others’ work and building on each others’ findings.
Awarded a best paper award at Eurovis 2009. Watch the video at http://www.youtube.com/watch?v=E9izFMJ5yms